Vegetative dysregulation in a groups with tumor of a brain and chronicle vessel encephalopathy patients - S. A. Tatarenko; B. N. Bein (Бюллетень сибирской медицины, 2009)
The sympathetic skin response and the spectral analysis of the heart rate variability at 25 patients with a tumor of a brain, at 39 patients with chronicle vessel encephalopathy, and also at 30 healthy examinees with the help of a computer complex "VNS-spectrum" are investigated. Quantitative shifts and the sign differences significative of change of descending influences of the suprosegmental vegetative centers, with imbalance sympathetic both parasympathetic nervous systems and humoral the channel of the regulation, distinct from norms, and also patients differing between groups a tumoral and vascular pathology are established. Changes of separate parameters are supplemented with distinctions within the group correlation mutual relation between parameters of the spectral analysis variability an heart rhythm.